Analisis Proses Produksi dan Pengaruhnya terhadap Kualitas Madu Hutan di Desa Mataiyang Sumbawa Barat, Indonesia - Sumarlin Sumarlin; Sahratullah Sahratullah (Jurnal Ilmiah Membangun Desa dan Pertanian, 2026)
Mataiyang Village in West Sumbawa Regency has significant potential as a producer of forest honey (Apis dorsata), with strong economic potential. However, declining production in recent years indicates inefficiencies in harvesting practices and unsustainable forest resource management. The objective was to analyze the harvesting process and its implications for forest honey quality using a mixed methods approach. Qualitative data were obtained through in-depth interviews with 10 key informants, while quantitative data were collected from 30 respondents using a structured questionnaire and analyzed using simple linear regression. The results indicate that traditional harvesting practices, such as tree felling, excessive smoke use, and the removal of entire hives, contribute to declines in bee populations and honey quality. Conversely, sustainable harvesting methods that maintain hive structure can double yields and maintain colony viability. Statistical analysis showed that the production process had a positive effect on honey quality, albeit with a low significance level of 5.8%. Honey produced with hygienic processing had higher water content and hygiene, meeting quality standards. This study recommends implementing sustainable harvesting techniques, hygienic processing, and modern equipment to increase sustainable production. These findings are expected to serve as the basis for developing Mataiyang Village into a competitive forest-honey center while supporting forest ecosystem conservation.